Analysis of Small Scale Broiler Production on Farmers’ Food Security in Southern Taraba, Taraba State, Nigeria - Danladi, Maiwayo Chuseh; Adekunle, Olayiwola Sikiru; Bulus, Filli Fave (Darul Yasin Al Sys, 2025)
This study analyzed Small scale broiler production on farmers’ food security in Southern Taraba, Taraba State, Nigeria. A multistage sampling technique was employed to collect primary data from 138 small-scale broiler farmers using well structure questionnaires. Data collected were analyzed using food security index, tobit regression model and the enterprise budgeting techniques such as gross margin, net farm income, net return on investment, gross ratio and profitability index. The findings revealed that 76.8% of the respondents were food secure. Cost and return showed average total revenue of N629,850.7 and N266,756.8 as total cost of production with a gross margin of N380,182.6. Net farm income of N363,093.9, net return on investment of N1.4, gross ratio of 0.4 and profitability index (PI) of 0.6 which signifies for every naira earned as revenue 60 kobo was return as net income. Effect of broiler production on farmers food security status showed that; cost of day old chicks, cost of drugs and income of farmers were significant at 1% while cost of transportation and cooperative membership were significant at 5% and cost of labour was significant at 10% and they influence food security either positively or negatively. It was concluded that broiler production is a profitable enterprise that aid broiler farmers to be food secured. It was recommended that efforts should be made for production input to be affordable and easily accessible by the farmers, agricultural cooperatives should be promoted and strengthened by providing members with the necessary input.